Role of microencapsulated Lactobacillus plantarum in alleviating intestinal inflammatory damage through promoting epithelial proliferation and differentiation in layer chicks - Cui, Yaoming; Huang, Peiyu; Duan, Haitao; Song, Shijia; Gan, Liping; Liu, Zhen; Lin, Qiaohan; Wang, Jinrong; Qi, Gunghai; Guan, Junjun (Frontiers in Microbiology, 2023)
The alleviating effects of Lactobacillus plantarum in microencapsulation (LPM) on lipopolysaccharide (LPS)-induced intestinal inflammatory injury were investigated in layer chicks. A total of 252 healthy Hy-Line Brown layer chicks were randomly divided into 6 groups. Birds were injected with saline or LPS except for the control, and the diets of birds subjected LPS were supplemented with nothing, L. plantarum, LPM and wall material of LPM, respectively. The viable counts of LPM reached 10 9 CFU/g, and the supplemental levels of L. plantarum, LPM and WM were 0.02 g (10 9 CFU), 1.0 g and 0.98 g, per kilogram feed, respectively. LPS administration caused intestinal damage in layer chicks, evidenced by increased proinflammatory factors accompanied with poor intestinal development and morphology (P ˂ 0.05). LPM/LPS significantly increased body weight, small intestine weight and length, villus height, villus height/crypt depth, mRNA relative expression of tight junction protein genes (P ˂ 0.05), and performed better than free L. plantarum. These findings could be attributed to the significant increase in viable counts of L. plantarum in small intestine (P ˂ 0.05), as well as the enhanced levels of Actinobacteriota, Lactobacillaceae and Lactobacillus in intestinal micobiota (P ˂ 0.05). Such results could further significantly increased goblet and PCNA+ cell percentage (P ˂ 0.05), and the mRNA relative expressions of epithelial cell, fast-cycling stem cell, quiescent stem cell, endocrine cell, Paneth cell, goblet and proliferative cell marker genes, including E-cadherin, Lgr-5, Bmi-1, ChA, Lysozome, Mucin-2, PCNA (P ˂ 0.05). Furthermore, the mRNA relative expressions of key genes involved in epithelial cell proliferation, namely c-Myc, Cyclin-1, Wnt-3, Lrp-5 and Olfm-4, exhibited significant upregulation compared to the LPS treatment, as well as the differentiating genes Notch-1 and Hes-1 (P ˂ 0.05). To sum up, microencapsulated L. plantarum supplementation could alleviate intestinal injury in layer chicks induced by LPS through promoting the proliferation and differentiation of intestinal epithelial cells, which could be attributed to the increase in viable count of L. plantarum in gut and optimization in intestinal microbial flora.